IMPACT OF PANDEMIC COVID 19 ON ANXIETY LEVEL OF PREGNANT WOMEN IN BENGKULU CITY - Kheli Fitria Annuril; Hermansyah Hermansyah (Proceeding B-ICON, 2022)
The mother's mental health during pregnancy can affect the psychological, emotional, and social development conditions for mothers and their babies, especially during a pandemic. This study aims to see how the mental state of pregnant women / anxiety levels during the Covid-19 pandemic in Bengkulu City. This type of research is an analytical survey with a Cross Sectional design. The population is all pregnant women in Bengkulu City. This research was conducted at the Independent Practice Midwife (BPM) Susi and the Mutiara Agma Betungan Clinic (BPM Herma Nelis) in September-November 2021. Sampling Technique, which is non-random sampling with purposive sampling method and the number of samples is 82 people. The research instrument uses a questionnaire, NuPDQ in Indonesian developed by Dr. Marci Lobel and colleagues and translated and tested for validity by Santoso, which was designed in a google form. . Data is processed with computer programs, presented univariately in the form of tables and graphs. Data analysis using proportional measures and measures of centering and Bivariate with Chi Square at a ? 5% and Multivariate analysis using multiple Logistic Regression Tests. The results of the study were obtained Most respondents experienced anxiety in the low category and there was no relationship between maternal characteristics and the anxiety levels of pregnant women during the Covid 19 pandemic